THE ROLE OF ISLAMIC EDUCATION IN FACING THE INDUSTRIAL ERA 4.0 - Chikmah, Lailatul; Rahmawati, Maulidia; Putri, Destya Anugrah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
The purpose of this study is to find out about Islamic education, the challenges and the role of Islamic education in the era of globalization and the industrial revolution 4.0. The method used in this study is a literature review and reference reference analysis related to the importance of Islamic education in facing globalization and the challenges of the industrial revolution 4.0. The results of this study conclude, with the aim of Islamic education to create a complete human being, as well as the role of Islamic education in the world of education which is carried out in intracurricular and extracurricular learning activities to create students with character capable of being the answer or solution to various challenges in the industrial era 4.0..